What do we gain when we listen to the patients? Comparison of psycholops with two nomothetic measures - Neves, Inês Teixeira das (2015)
This research aims to explore the clinical usefulness of an individualized outcome measure, the Psychological Outcome Profiles (PSYCHLOPS). PSYCHLOPS is selfreport measure that invites the patient to build his own outcome questionnaire. Our goal is to understand to what extent the items indicated by the patient add qualitative information, when compared with standardized outcome measures. A total of 107 adult patients in treatment in two sites filled in the PSYCHLOPS and two standardized measures (CORE-OM and PHQ-9). A total of 279 patient-generated items where analysed and categorized in 65 content sub-themes. Results show that “Work – related problems” was the most common sub-theme indicated by patients. Approximately one quarter of sub-themes (26%) were not found in CORE-OM items and 66% (n=43) were not found in PHQ-9 items. Seventy nine (74%) patients reported at least one problem that is not covered in CORE-OM. Almost the entire sample (96.2% of the patients) reported at least one response that did not map to a PHQ-9 item. Throughout this study it was revealed the complexity of the answers given by the patients; O que ganhamos ao ouvir os pacientes? Comparação do PSYCHLOPS com duas medidas nomotéticas. Resumo: Este estudo tem como objetivo explorar a utilidade clínica de uma medida individualizada, o Psychological Outcome Profiles (PSYCHLOPS). O PSYCHLOPS é uma medida de auto-relato que convida o paciente a construir o seu próprio questionário. O nosso objetivo é compreender até que ponto os itens indicados pelo paciente acrescentam informação qualitativa, quando comparados com medidas nomotéticas. Um total de 107 pacientes clínicos em dois locais preencheram o PSYCHLOPS e duas medidas estandardizadas (CORE-OM e PHQ-9). Um total de 279 itens criados pelos pacientes foram analisados e categorizados em 65 subtemas. Os resultados indicam que “Problemas relacionados com o trabalho” foi o subtema mais comum descrito pelos pacientes. Aproximadamente ¼ dos subtemas (26%) não estão representados nos itens do CORE-OM e 66% (n=43) não estão representados nos itens do PHQ-9. Setenta e nove pacientes (74%) relatam pelo menos uma resposta não representada nos itens do CORE-OM. Praticamente toda a amostra (96.2% dos pacientes) relata pelo menos uma resposta não representada nos itens do PHQ-9. Ao longo deste estudo foi demonstrada a complexidade das respostas dadas pelos pacientes.